Prevalência de síndrome metabólica entre os pacientes atendidos no ambulatório de nutrição de um hospital escola - ALVES, Rogério de Jesus da Cruz (2023)
Objective: To identify the prevalence of metabolic syndrome in adult patients treated at the nutrition clinic of a teaching hospital in the city of Belém-Pará. Methods: Cross-sectional, observational, quantitative and descriptive study based on data collection from electronic medical records. Sociodemographic, clinical and anthropometric information on adult patients of both sexes was recorded. The diagnosis of metabolic syndrome was made according to the criteria adopted by the National Cholesterol Education Program's Adult Treatment Panel III of 2001. The Shapiro-Wilk test was used to assess the normality of the variables. In the descriptive statistics, the proportion and measures of central tendency were presented and in the analytical one, the t or Mann-Whitney comparison tests. A significance level of 5% was adopted. Results: The medical records of 116 patients were analyzed, 79.3% (n=92) were female and 20.7% (n=24) were male (p<0.001). The mean age was 46.6 years and 88.8% of the population was sedentary (p<0.001). Diabetes mellitus (29.4%) and arterial hypertension (25.4%) prevailed significantly (p<0.05). Excess weight occurred in 90.5% of patients (p<0.001). Low HDL cholesterol and elevated LDL-cholesterol and non-HDL-cholesterol were observed in 69.0%, 70.6% and 89.7% of patients, respectively. There was a positive correlation between fasting glucose and glycated hemoglobin (r=0.81, p<0.05) and between LDL-cholesterol and total cholesterol (r=0.85, p<0.05). A quarter of the patients (26.2%) had metabolic syndrome. Conclusion: Most patients did not present MS. A considerable portion had one or two components of the metabolic syndrome, a condition that, by themselves, already increases the risk of CVD.